Autonomy and participation (IPA) in research on people with physical disabilities - Marlena Duda (Studia z Teorii Wychowania)
This article focuses on the phenomenon of autonomy of people with physical disabilities, which has been relatively little described in the Polish literature to date. The undertaken considerations are of a review nature and present a theoretical approach towards the issue of autonomy and participation from the perspective of International Classification of Functioning, Disability and Health (ICF). They are supplemented by the presentation of the results of the selected empirical studies. The article is based on literature review and concerns the nature of autonomy and physical disability. As a result of the conducted analyses it can be inferred that autonomy and participation of people with disabilities is to the greatest extent shaped by contextual factors (personal and environmental ones). There is also a positive relationship of the analysed variables with life satisfaction and its quality, adaptation to disability as well as wisdom and a negative relationship with secondary health complications and mobility limitations.